Outdoor Space as Integral Component in Home making at Low-cost Housing in Bangsar - Zulkifli, Adeeb; Aminuddin, Asrul (MAJ - Malaysia Architectural Journal, 2020)
Low-cost housing is often subjected to minimum dwelling space and this forces the life of its residents to spill outdoors. Outdoor space provided at multilevel low-cost housing especially is usually the product of an afterthought by the designer and developer. It is often stereotyped with poor condition and if not neglected maintenance-wise, it is often abused for other purposes. This also affects the perception and usage of the residents of this outdoor space provided at their home. The role of outdoor space at low-cost housing is often overlooked, while in reality, the provision of this outdoor space is vital for the residents as it helps the residents in the process of home making and to define and achieve the quality of life, especially in low-cost housing. Therefore, this paper aims to study the residents’ usage of outdoor spaces that can contribute to the wellbeing and home making of the residents.